Notes on the spider genus Dysdera Latreille, 1804 (Araneae: Dysderidae) in Central Asia - Fomichev, Alexander A.; Marusik, Yuri M. (Zootaxa, 2021)
A new species, Dysdera mikhailovi sp. nov. (♀), is described from Tajikistan (nr. Dushanbe). A poorly known species Dysdera subcylindrica Charitonov, 1956 from Central Asia is redescribed based on newly collected material. Dysdera dushengi Lin, Chang et Li, 2020, known from western Xinjiang (China) is reported from Kazakhstan for the first time. (Re)descriptions, figures, diagnoses and distribution maps of all the studied species are provided.